Ethylene‐activated MdPUB24 mediates ubiquitination of MdBEL7 to promote chlorophyll degradation in apple fruit - Wei, Yun; Jin, Juntong; Xu, Yaxiu; Liu, Weiting; Yang, Guangxin; Bu, Haidong; Li, Tong; Wang, Aide (The Plant journal : for cell and molecular biology, 2021)
SUMMARY Chlorophyll (Chl) degradation is a natural phenomenon that occurs during ripening in many fleshy fruit species, and also during fruit storage. The plant hormone ethylene is a key factor in promoting Chl degradation during fruit storage, but the mechanisms involved in this induction are largely unknown. In this study, an apple (Malus domestica) BEL1‐LIKE HOMEODOMAIN transcription factor 7 (MdBEL7), potentially functioning as a transcriptional repressor of the Chl catabolic genes (CCGs), including MdCLH, MdPPH2 and MdRCCR2, was identified as a partner of the ethylene‐activated U‐box type E3 ubiquitin ligase MdPUB24 in a yeast library screen. Yeast‐two‐hybrid, co‐immunoprecipitation and luciferase complementation imaging assays were then used to verify the interaction between MdBEL7 and MdPUB24. In vitro and in vivo ubiquitination experiments revealed that MdPUB24 functions as an E3 ubiquitin ligase to ubiquitinate MdBEL7, thereby causing its degradation through the 26S proteasome pathway. Transient overexpression of MdPUB24 in apple fruit led to a decrease in MdBEL7 abundance and increased expression of CCG genes, including MdCLH, MdPPH2 and MdRCCR2, as well as greater Chl degradation. Taken together, the data indicated that an ethylene‐activated U‐box type E3 ubiquitin ligase MdPUB24 directly interacts with and ubiquitinates MdBEL7. Consequent degradation of MdBEL7 results in enhanced expression of MdCLH, MdPPH2 and MdRCCR2, and thus Chl degradation during apple fruit storage. Our results reveal that an ethylene‐MdPUB24‐MdBEL7 module regulates Chl degradation by post‐translational modification during apple fruit storage. Significance Statement The ethylene‐activated U‐box type E3 ubiquitin ligase MdPUB24 from apple can directly interact with and ubiquitinate MdBEL7, leading to the degradation of the latter and enhanced expression of MdCLH, MdPPH2 and MdRCCR2, and thus can positively regulate chlorophyll degradation during apple fruit storage. This represents a regulatory module leading to enhancing Chl degradation during apple storage associated with a specific and pronounced post‐translational modification.